2013
DOI: 10.1637/10426-101712-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aflatoxins on Performance and Exocrine Pancreas of Broiler Chickens

Abstract: The aim of this research was to evaluate, on a weekly basis, the effects of aflatoxins on the activity of digestive enzymes (alpha-amylase, lipase, and trypsin) in the pancreas as well as on the performance and histology of pancreas in broiler chickens over the course of 42 days. One thousand and eighty 1-day-old male Cobb broilers were divided into four treatments with 18 replicates and 15 birds per replicate (i.e., 270 broilers per treatment). Treatments were established according to the amount of aflatoxins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…It confirms that BWG is not solely influenced by FI under mycotoxicosis and therefore impact of different toxins on other factors such as nutrient absorption might indirectly affect BWG. This result is consistent with those reported by Marchioro et al (2013) that aflatoxin increased digestive enzymes of broilers, but did not improve their growth performance, indicating that absorption is affected by existence of mycotoxins in the diet. The improving role of 0.05% E-GM to neutralize the deleterious effects of mycotoxicosis on performance has been previously reported by Aravind et al (2003) and Modirsanei et al (2004).…”
Section: Discussionsupporting
confidence: 93%
“…It confirms that BWG is not solely influenced by FI under mycotoxicosis and therefore impact of different toxins on other factors such as nutrient absorption might indirectly affect BWG. This result is consistent with those reported by Marchioro et al (2013) that aflatoxin increased digestive enzymes of broilers, but did not improve their growth performance, indicating that absorption is affected by existence of mycotoxins in the diet. The improving role of 0.05% E-GM to neutralize the deleterious effects of mycotoxicosis on performance has been previously reported by Aravind et al (2003) and Modirsanei et al (2004).…”
Section: Discussionsupporting
confidence: 93%
“…Histological studies of pancreatic lesions in broilers with RSS revealed fibrosis, inflammation, vacuolar changes in the exocrine compartment, degeneration of acinar cells and loss of zymogen granules (Qamar et al 2013). In pigeons, exocrine pancreas disease produced voluminous, coloured faeces and weight loss (Amann et al 2006), and when aflatoxins are present in the diet, histological changes in the pancreas are observed, together with effects on performance and nutrient absorption (Marchioro et al 2013). Together, these findings establish a relationship between pancreatic damage and signs of malabsorption, and, more importantly, a relationship between pancreatic damage and RSS.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is believed that aflatoxicosis results in reduced activity of several digestive enzymes such as amylase, trypsin, chymotrypsin and lipase, resulting in malabsorption of nutrients in the small intestine. Marchioro et al (2013) observed an increased pancreatic activity of lipase and α-amylase in birds fed 1.7 and 2.8 mg AF/kg diet, while the specific activity of trypsin was only negatively affected when birds were fed 2.8 mg AF/kg diet.…”
Section: Aflatoxin In Poultrymentioning
confidence: 85%
“…Gowda et al (2008) demonstrated that broilers fed 1 mg/kg of AFB1 for 21 days significantly lower feed intake, and weight gain, and increased relative liver weight. Marchioro et al (2013) reported that when broilers were fed up to 2.8 mg of AFB1/kg, there was a negative effect on all performance parameters. Also, pancreatic activity of lipase and α-amylase were significantly increased, affecting the digestibility of the diet, thus leading to losses in performance and productivity.…”
Section: Aflatoxin In Poultrymentioning
confidence: 99%